2009
DOI: 10.1016/j.hrthm.2009.10.015
|View full text |Cite
|
Sign up to set email alerts
|

Ripple mapping: Making electroanatomic mapping user-friendly

Abstract: With the introduction of electroanatomic mapping systems, electrical voltage maps of the chamber of interest and activation maps of arrhythmias have emerged as invaluable tools for successful ablation of focal and reentrant arrhythmias.(1) In reentrant rhythms that cause hemodynamic instability, substrate modification has been demonstrated to achieve meaningful results.(2,3) In arrhythmias where a scar serves as the substrate for reentry, activation maps and voltage maps must be acquired and displayed separate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…As no interpolation is carried out by the Ripple-mapping algorithm, the more points are collected, the better the resolution of the map. This has been previously highlighted [21], and was clear in the two patients where we performed high-density mapping using the Penta-Ray catheter and CONFIDENSE TM to automatically collect/sample points. However, even in the two patients where point density was lower we were also able to identify the culprit areas.…”
Section: Discussionmentioning
confidence: 58%
“…As no interpolation is carried out by the Ripple-mapping algorithm, the more points are collected, the better the resolution of the map. This has been previously highlighted [21], and was clear in the two patients where we performed high-density mapping using the Penta-Ray catheter and CONFIDENSE TM to automatically collect/sample points. However, even in the two patients where point density was lower we were also able to identify the culprit areas.…”
Section: Discussionmentioning
confidence: 58%
“…Our previous study demonstrated that RM achieved a high diagnostic rate for complex AT after cardiac surgery 14 . The reason for the higher diagnostic level and termination rate was that RM overcame the limitations of LAT mapping, such as incorrect color interpolation, arbitrary WOI setting, and mis‐annotation of the LAT 9 . Yajishita et al.…”
Section: Discussionmentioning
confidence: 99%
“…14 The reason for the higher diagnostic level and termination rate was that RM overcame the limitations of LAT mapping, such as incorrect color interpolation, arbitrary WOI setting, and mis-annotation of the LAT. 9 Yajishita et al reported that the utility of RM and LAT mapping was superior to that of LAT mapping alone in the diagnostic accuracy of the AT mechanism, regardless of AT categories. 15 The challenges in understanding activation maps in complex scar-related AT require a new mapping algorithm to interpret complicated 3D activation map.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation